Dihydromyricetin suppresses endothelial NLRP3 inflammasome activation and attenuates atherogenesis by promoting mitophagy - Qin Hu; Chengying Li; Ting Zhang; Long Yi; Yifan Shan; Xiangyu Ma; Tongjian Cai; Li Ran; Hui Shen; Yafei Li (Lipids in Health and Disease, 2024)
Abstract Background NOD-like receptor protein 3 (NLRP3) inflammasome activation is indispensable for atherogenesis. Mitophagy has emerged as a potential strategy to counteract NLRP3 inflammasome activation triggered by impaired mitochondria. Our previous research has indicated that dihydromyricetin, a natural flavonoid, can mitigate NLRP3-mediated endothelial inflammation, suggesting its potential to treat atherosclerosis. However, the precise underlying mechanisms remain elusive. This study sought to investigate whether dihydromyricetin modulates endothelial mitophagy and inhibits NLRP3 inflammasome activation to alleviate atherogenesis, along with the specific mechanisms involved. Methods Apolipoprotein E-deficient mice on a high-fat diet were administered daily oral gavages of dihydromyricetin for 14 weeks. Blood samples were procured to determine the serum lipid profiles and quantify proinflammatory cytokine concentrations. Aortas were harvested to evaluate atherosclerotic plaque formation and NLRP3 inflammasome activation. Concurrently, in human umbilical vein endothelial cells, Western blotting, flow cytometry, and quantitative real-time PCR were employed to elucidate the mechanistic role of mitophagy in the modulation of NLRP3 inflammasome activation by dihydromyricetin. Results Dihydromyricetin administration significantly attenuated NLRP3 inflammasome activation and vascular inflammation in mice on a high-fat diet, thereby exerting a pronounced inhibitory effect on atherogenesis. Both in vivo and in vitro, dihydromyricetin treatment markedly enhanced mitophagy. This enhancement in mitophagy ameliorated the mitochondrial damage instigated by saturated fatty acids, thereby inhibiting the activation and nuclear translocation of NF-κB. Consequently, concomitant reductions in the transcript levels of NLRP3 and interleukin-1β (IL-1β), alongside decreased activation of NLRP3 inflammasome and IL-1β secretion, were discerned. Notably, the inhibitory effects of dihydromyricetin on the activation of NF-κB and subsequently the NLRP3 inflammasome were determined to be, at least in part, contingent upon its capacity to promote mitophagy. Conclusion This study suggested that dihydromyricetin may function as a modulator to promote mitophagy, which in turn mitigates NF-κB activity and subsequent NLRP3 inflammasome activation, thereby conferring protection against atherosclerosis.